The Structure of Public Debt and the Criteria of Its Sustainability - Paweł Piątkowski (Annales Universitatis Mariae Curie-Skłodowska Sectio H, Oeconomia, 2022)
Theoretical background: Sustainable development is a wide and developing economic concept. The sustainability of public finances is one of its basic parts. Sustainable public finances are still perceived rather narrowly in terms of their impact on the financial stability of the state. Such an approach to them narrows their perception and should be extended to other aspects such as influence on social and ecological problems of development. Sustainable public debt is and will continue to be a foundation of sustainable public finances. It should be assessed as sustainable public debt, taking into account both its impact on the sustainability of public finances as well as the possibility of providing public services in the future and the achievement of economic, social, and environmental goals of sustainable development.